Two operatic seasons of brothers Mingotti in Ljubljana - Metoda Kokole (De Musica Disserenda, 2015)
The brothers Angelo and Pietro Mingotti between 1736 and 1746 based in Graz organised during this period also two operatic seasons in Ljubljana, one in 1740 and the other in 1742. Two serious operas (Artaserse andRosmira) with comic intermezzi (Pimpinone e Vespetta) were produced in 1740 by Angelo Mingotti. Two years later, just before leaving Graz for the engagements in the North, Pietro Mingotti brought another two operas to Ljubljana, Didone abbandonata and Il Demetrio. The former was performed also in 1744 in Hamburg with some of the same singers who apparently used mostly an earlier score, possibly first checked out in Graz and Ljubljana. The comparative analysis of productions in Ljubljana confirms that these operas were mostly pasticcios. Pietro’s Didone abbandonata, however, shows that he was more and more attentive also to music integrity of his productions, choosing to use music by mostly one composer, for example Paolo Scalabrini in the case of Didone.